Sustainable Production Management in Circular Economy Supply Chains - Zulki Zulkifli Noor (International Journal of Industrial Engineering and Management)
The transition to circular economy (CE) principles represents a critical challenge for sustain- able industrial development. This study investigates the implementation and effectiveness of sustainable production management strategies within CE-based supply chains, aiming to develop a comprehensive framework for successful integration. A concurrent triangulation mixed-methods approach was employed, integrating quantitative sustainability metrics from 100 manufacturing companies with qualitative case studies of 10 industry leaders through systematic data cross-validation. Data collection spanned 24 months (2022-2023), measuring resource utilization, waste reduction, energy efficiency, and economic performance. Analysis included statistical evaluation of performance metrics and thematic analysis of implemen- tation factors. Companies implementing CE principles demonstrated significant improve- ments, including 24.6% reduction in raw material consumption, 31.8% decrease in waste generation, and 27.5% reduction in carbon emissions. Economic benefits included a 12.4% increase in profitability and 22.3% return on investment. Leadership commitment (92%) and stakeholder engagement (88%) emerged as critical success factors, while technical barri- ers presented the most significant challenges (severity score 4.2/5.0). Sustainable production management in CE supply chains yields substantial environmental and economic benefits. The study provides an empirically validated framework for organizations transitioning to- wards circular production models, while highlighting the importance of organizational factors in successful implementation.